FAM21C Promotes Hepatocellular Carcinoma Invasion and Metastasis by Driving Actin Cytoskeleton Remodeling via Inhibiting Capping Ability of CAPZA1 - Lu, Yao; Huang, Deng; Wang, Baolin; Zheng, Bowen; Liu, Jialong; Song, Juxian; Zheng, Shuguo (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is characterized by a high incidence of metastasis. The dynamic remodeling of the actin cytoskeleton plays an important role in the invasion and migration of HCC cells. In previous studies, we found that CAPZA1, a capping protein, can promote EMT of HCC cells by regulating the remodeling of the actin filament (F-actin) cytoskeleton, thus promoting the invasion and migration of HCC cells. In this study, we found that FAM21C may have a regulatory effect on CAPZA1, and we conducted an in-depth study on its potential regulatory mechanism. First, we found that FAM21C is highly expressed in HCC tissues and its high expression could promote the malignant progression of HCC. Meanwhile, the high expression of FAM21C promoted the invasion and migration of HCC cells in vitro and in vivo. Further, FAM21C interacted with CAPZA1, and their binding inhibited the capping capacity of CAPZA1, thus promoting the invasion and migration of HCC cells. This effect of FAM21C was abolished by mutating the CP-interacting (CPI) domain, the CAPZA1 binding site on FAM21C. In conclusion, high expression of FAM21C in HCC tissues can promote malignant progression of HCC and its potential mechanism involves FAM21C inhibition of CAPZA1 capping capacity by binding to CAPZA1, which drives F-actin cytoskeleton remodeling, and thus promotes invasion and migration of HCC cells.